Kreativitas Guru PAI Dalam Meningkatkan Pembelajaran Agama Di SMP Negeri 1 Darussalam Aceh Besar - Anida, Anida; Ristawati, Ristawati; Mahmudi, Mahmudi; Ramadhan, Muhammad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2024)
Teachers have a very big role, both in improving the quality of education and developing students' interest in learning. Thus, teachers must be creative in teaching so that the learning objectives are achieved well. In this research, the problem is how to plan creativity in teaching, implement methods and models as well as supporting and inhibiting factors for developing religious teacher creativity in student learning at SMP Negeri 1 Darussalam Aceh Besar. This research uses an analytical description method with the type of field research and is supported by references related to the themes discussed in this thesis (library research). The subjects of this research were class II students at SMP Negeri 1 Darussalam Kab. Aceh Besar. The data collection technique used was interviews assisted by observation and documentation. Based on the results of research in the field, it shows that the religion teacher at SMP Negeri 1 Darussalam before the learning process carried out MGMP and formulated learning objectives, chose books that had a high weight, the implementation used relevant teaching methods and media to stimulate students' thinking power, apart from that the teacher utilize the learning media available at school and also create your own learning media. Thus, the methods and materials of religious teachers in improving student learning achievement are quite optimal and also religious teachers have sufficient creativity in the teaching and learning process.